PDGF-C Is a Proinflammatory Cytokine that Mediates Renal Interstitial Fibrosis - Eitner, Frank (American Society of Nephrology, 2008)
PDGF-C is a potent mitogen for fibroblasts in vitro. Transgenic PDGF-C overexpression in the heart or liver induces organ fibrosis, and PDGF-C expression is upregulated at sites of interstitial fibrosis in human and rat kidneys; however, the effect of inhibiting PDGF-C on the development of renal fibrosis in vivo is unknown. Renal fibrosis was induced in C57BL/6 mice by unilateral ureteral obstruction (UUO), and then mice were treated with neutralizing anti–PDGF-C antiserum or nonspecific IgG. An increase in PDGF-C expression was observed in fibrotic areas after UUO, contributed in large part by infiltrating macrophages. Treatment with anti–PDGF-C reduced renal fibrosis by 30% at day 5 and reduced interstitial myofibroblast accumulation by 57%. In vitro, PDGF-C was a potent mitogen for renal fibroblasts and induced chemokine expression. In vivo, anti–PDGF-C treatment produced a decrease in the expression of the renal chemokines CCL2 and CCL5 (85 and 67% reductions, respectively), accompanied by a significant decrease in leukocyte infiltration and CCR2 mRNA expression. Further supporting a role of PDGF-C in renal fibrosis, PDGF-C(−/−) mice demonstrated a reduction in fibrosis and leukocyte infiltration in response to UUO compared with wild-type littermates. In conclusion, specific neutralization or lack of PDGF-C reduces the development of renal inflammation and fibrosis in obstructed mouse kidneys. Leukocyte-derived PDGF-C induces chemokine expression, which may lead to the recruitment of additional leukocytes, creating an amplification loop for renal inflammation and fibrosis.